2015
DOI: 10.1002/cmmi.1653
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43‐targeted T1 contrast agent for MRI diagnosis of glioma

Abstract: Glioblastoma multiforme is the most aggressive form of brain tumor. Early and accurate diagnosis of glioma and its borders is an important step for its successful treatment. One of the promising targets for selective visualization of glioma and its margins is connexin 43 (Cx43), which is highly expressed in reactive astrocytes and migrating glioma cells. The purpose of this study was to synthesize a Gd-based contrast agent conjugated with specific antibodies to Cx43 for efficient visualization of glioma C6 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Intriguingly, a combination of this Cx43 antibody with TMZ completely abolishes the antitumor effect of this antibody while combination treatment with γ-irradiation greatly inhibits tumour development and prolongs survival median to 60 days versus 38 days [ 172 ]. Recently, a magnetic resonance imaging (MRI) study further shows that uptake of Gd-based contrast agent with the same monoclonal Cx43 antibody is more than 4 times higher than nonspecific IgG-contrast agent and this Cx43 antibody conjugated agent markedly enhances visualization of glioma in vivo [ 173 ]. Although the specific molecular mechanism of this antibody is unknown, this Cx43-targeting monoclonal antibody could be developed as a potential drug and/or diagnostic agent for glioma therapies.…”
Section: Connexin and Pannexin Channels In Potential Cancer Therapmentioning
confidence: 99%
“…Intriguingly, a combination of this Cx43 antibody with TMZ completely abolishes the antitumor effect of this antibody while combination treatment with γ-irradiation greatly inhibits tumour development and prolongs survival median to 60 days versus 38 days [ 172 ]. Recently, a magnetic resonance imaging (MRI) study further shows that uptake of Gd-based contrast agent with the same monoclonal Cx43 antibody is more than 4 times higher than nonspecific IgG-contrast agent and this Cx43 antibody conjugated agent markedly enhances visualization of glioma in vivo [ 173 ]. Although the specific molecular mechanism of this antibody is unknown, this Cx43-targeting monoclonal antibody could be developed as a potential drug and/or diagnostic agent for glioma therapies.…”
Section: Connexin and Pannexin Channels In Potential Cancer Therapmentioning
confidence: 99%
“…The value of Cx43 in glioma diagnosis and therapy is beginning to be recognized. Abakumova (103) demonstrated that the Cx43-targeted T1 contrast agent may efficiently visualize glioma C6 and its borders in vitro and in vivo. MAbE2Cx43 s was covalently associated with the Phthalosens derivative photosensitizer delivery of fluorescent agents to the glioma tissue.…”
Section: Facilitating Disease Diagnosis and Therapymentioning
confidence: 99%
“…Concerning tumor targeting, after the seminal papers in which conjugates of poly‐ L ‐lysine with DTPA‐Gd chelates (PLL‐DTPA‐Gd) were used for tumor diagnosis of mammary adenocarcinoma and glioma in rodent models, further improvements of MRI diagnosis of tumor were pursued through active targeting. An example is represented by the system proposed by Abakumova et al who synthesized a conjugate of the monoclonal antibody (mAb) to Cx43 and poly‐lysine‐DTPAmonoamide‐Gd(III) (see Figure B) for the efficient in vivo visualization of glioma C6. The total Gd(III) loading was about 520 ions per mAb, and the molecular weight of the targeted CA was about 850 kDa.…”
Section: Introductionmentioning
confidence: 99%